Pemanfaatan Kalium Permanganat Berbasis Serbuk Gergaji untuk Memperpanjang Masa Simpan dan Mutu Jambu Biji Crystal - Rina Ningtyas; Mahdayani Budianto Harahap Harahap (Ma'soem University, 2026)
The ‘Crystal’ guava is an Indonesian tropical fruit with high nutritional value and strong potential for global market competitiveness. However, its short shelf life remains a major challenge,and requiring effective postharvest handling strategies. This study aims to analyze the effectiveness of potassium permanganate (KMnO?) as an ethylene absorber, using sawdust as an inexpensive and readily available substrate, to maintain the quality and shelf life of ‘Crystal’ guava stored in packaging at room temperature (26–30°C). The experiment was arranged in a completely randomized design (CRD) with three treatments—P0 (control), P1 (6% KMnO?) and P2 (12% KMnO?)—and two replications; data were analyzed by ANOVA at the 5% level followed by Duncan's multiple range test. Quality evaluations included weight loss, Total Soluble Solids (TSS), vitamin C content, and organoleptic attributes. The results showed that KMnO? significantly affected weight loss, TSS, and vitamin C content. The best treatment was P1 (sawdust + 6% KMnO?), which resulted in a weight loss of 4.297%, TSS of 7.58 °Brix, and vitamin C content of 13.75 mg/100 g. Based on organoleptic assessment, the fruit remained acceptable to consumers in terms of color, taste, and aroma up to 6 days after storage (DAS), and in terms of texture up to 12 DAS, particularly in the 6% and 12% KMnO? treatments. Overall, KMnO? supported by a sawdust matrix successfully reduced weight loss up to 18 DAS and preserved TSS, vitamin C content, and organoleptic quality up to 12 DAS compared with the control, demonstrating its effectiveness in improving the postharvest quality and extending the shelf life of ‘Crystal’ guava.